A detailed review on non-orthogonal multiple accessbased spatial modulation systems. Issue 2 (30th April 2020) - Jadhav, Kishor Purushottam; Mahor, Amita; Bhowmick, Anirban; N., Anveshkumar
Abstract : Purpose: Non-orthogonal multiple access (NOMA) is a much hopeful scheme, which is deployed to enhance the spectral efficiency (SE) significantly, and it also enhances the massive access that has attained substantial concern from industrial and academic domains. However, the deployment of superposition coding (SC) at the receiver side resulted in interference. For reducing this interference, "multi-antenna NOMA" seems to be an emerging solution. Particularly, by using the channel state information at the transmitter, spatial beam forming could be deployed that eliminates the interference in an effective manner. Design/methodology/approach: This survey analyzes the literature review and diverse techniques regarding the NOMA-based spatial modulation (SM) environment. It reviews a bunch of research papers and states a significant analysis. Initially, the analysis depicts various transmit antenna selection techniques that are contributed in different papers. This survey offers a comprehensive study regarding the chronological review and performance achievements in each contribution. The analytical review also concerns on the amplitude phase modulation (APM) selection schemes adopted in several contributions. Moreover, the objective functions adopted in the reviewed works are also analyzed. Finally, the survey extends with various research issues and its gaps that can be useful for the researchers to promote improved future works on NOMA-based SM. Findings: This paper contributes to a review related to NOMA-based SM systems. Various techniques and performance measures adopted in each paper are analyzed and described in this survey. More particularly, the selection of transmission antenna and APM are also examined in this review work. Moreover, the defined objective function of each paper is also observed and made a chronological review as well. Finally, the research challenges along with the gaps on NOMA-based SM systems are also elaborated. Originality/value: This paper presents a brief analysis of NOMA-based SM systems. To the best of the authors' knowledge, this is the first work that uses NOMA-based SM systems to enhance SE.